Ultralow fouling membranes by surface modification with functional polydopamine. (February 2018) - Tripathi, Bijay P.; Das, Pritam; Simon, F.; Stamm, Manfred
Graphical abstract: Highly permeable and antifouling membranes were prepared by simple molecular functionalization and zwitterionization of polydopamine layers on polysulfone membrane. Highlights: Ultra-low fouling membranes were prepared by molecular functionalization. Polydopamine was used to graft small active molecules and functionalization. Prepared membranes showed high permeation and antifouling properties. Abstract: We report a facile, versatile, and novel approach for the design of ultralow fouling membranes via mussel-inspired molecular functionalization and zwitterionization. Using mussel-inspired polydopamine (PDA) coatings on polysulfone microporous membranes, active molecules with tertiary amine functionality ( N, N -dimethylethylenediamine (DMDA)) were grafted via Michael addition through primary amine groups. The DMDA-functionalized membrane was further reacted with 1, 3-propane sultone to obtain zwitterionic membrane. The variation of surface chemistry and surface wettability upon molecular functionalization was monitored with X-ray photoelectron spectroscopy (XPS) and water contact angle measurements. Following molecular functionalization, the membranes became more hydrophilic due to strong surface hydration with PDA, and zwitterionic functional groups. The functionalized membranes showed ultralow bovine serum albumin (BSA) protein adsorption and high flux recovery after protein filtration. The versatile nature of PDA modification along with its molecular functionalization allows for the design of ultralow fouling surfaces, making this a promising membrane modification technique for water filtration and separation, but also for other antifouling applications.